2007
DOI: 10.1038/modpathol.3800941
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Y chromosome in human placental site trophoblastic tumor

Abstract: Placental site trophoblastic tumor is a neoplasm of extravillous intermediate trophoblast at the implantation site, preceded in the majority of cases by a female gestational event. Our pilot investigation suggested that the development of this tumor might require a paternally derived X chromosome and the absence of a Y chromosome. Twenty cases of placental site trophoblastic tumor were included in this study. Genotyping at 15 polymorphic loci and one sex determination locus was performed by multiplex PCR follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Among these five tumors was a PSTT. This finding is in contrast to a previous report demonstrating that none of 13 PSTTs harbored the AMELY [12]. The discrepancy is likely explained by the larger sample size and the additional Y markers employed in this study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Among these five tumors was a PSTT. This finding is in contrast to a previous report demonstrating that none of 13 PSTTs harbored the AMELY [12]. The discrepancy is likely explained by the larger sample size and the additional Y markers employed in this study.…”
Section: Resultscontrasting
confidence: 99%
“…On the contrary, more than 85% of patients with PSTTs were found by history records or genetic analysis to have had a female antecedent gestation. Moreover, a recent study using the Amelogenin assay demonstrated the presence of a X-chromosome and absence of a Y in a small series of PSTTs [12], raising the possibility that a Y-chromosomal complement may be preferentially deleted in PSTTs. In this paper we describe our findings in a larger number of PSTTs, as well as other types of GTNs including choriocarcinomas and ETTs.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of morphologic and immunohistochemical studies, PSN may represent the benign counterpart of ETT and EPSR the counterpart of PSTT. This study was based on results from previous reviews that the unique genetic requirement for neoplastic proliferation in PSTT was the presence of paternal X chromosome and reasoned that if EPSR is a benign counterpart of PSTT or a background condition from which PSTT develops, a similar genetic requirement should exist in EPSR (18,19). Furthermore, lack of a clear biologic link between PSTT and EPSR was demonstrated in a recent study (17).…”
Section: Apsn and Association With Malignant Gtdmentioning
confidence: 99%
“…The intermediate trophoblastic cells leave the placenta to restructure the spiral arterioles in order to decrease the blood flow resistance toward the placenta ( 4 , 5 ). PSTTs come from these spiral arterioles ( 6 ).…”
Section: Discussionmentioning
confidence: 99%